Development and validation of stability indicating RP-HPLC method for nebivolol by using the DOE approach - Ghongade, Anant; Barot, Shruti (Journal of Applied Pharmaceutical Research, 2025)
Background: Nebivolol (NBV), classified as a third-generation β1-adrenergic receptor antagonist, is commonly prescribed for managing hypertension. Accurate and prompt quantification of NBV in bulk materials and pharmaceutical formulations is crucial for quality assurance. This research focuses on developing and validating a stability-indicating RP-HPLC method for the quantification of NBV, with an emphasis on sensitivity, precision, accuracy, and robustness. Methodology: A stability-indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method was established using an Agilent 1260 Infinity II HPLC system equipped with a Diode Array Detector (DAD). The chromatographic analysis was conducted on an Agilent Zorbax Bonus RP column (250 × 4.6 mm, 5 µm). The mobile phase comprised acetonitrile and 0.1% perchloric acid in a 55:45 (v/v) ratio, delivered at a flow rate of 1 mL/min. Detection was performed at a wavelength of 282 nm. The method underwent validation according to the guidelines provided by the International Council for Harmonisation (ICH), including assessments of linearity, precision, accuracy, robustness, and forced degradation studies. Results and Discussion: This method demonstrated improved sensitivity, shorter run time (retention time of 4.22 min), and high precision. Forced degradation studies confirmed Nebivolol’s instability under alkaline (15.94%) and oxidative (8.57%) conditions, highlighting the method’s stability-indicating capability. The method also gives robust linearity across the concentration range of 80–120 µg/mL, with a correlation coefficient (r²) of 1.00. The limits of detection (LOD) and quantification (LOQ) were determined to be 0.55 µg/mL and 1.61 µg/mL, respectively. Conclusion: The proposed RP-HPLC method proved to be reliable, precise, and stability-indicating, making it a valuable tool for the quality control and stability assessment of Nebivolol formulations in pharmaceutical settings.